Mitochondrion-targeting PEGylated BODIPY dyes for near-infrared cell imaging and photodynamic therapy. Issue 8 (26th January 2022) - Badon, Isabel Wen; Kim, Chanwoo; Lim, Jong Min; Mai, Duy Khuong; Vales, Temmy Pegarro; Kang, Dongho; Cho, Sung; Lee, Joomin; Kim, Ho-Joong; Yang, Jaesung
Abstract : We report the synthesis of NIR-absorbing and mitochondrion-targeting BODIPY dyes, which exhibited high phototoxicity toward cancer cells while affording cell imaging. Abstract : A series of 4, 4-difluoro-4-bora-3 a, 4 a -diaza- s -indacene-based photosensitizers (AmB X I, X = H, M, Br) featuring a cationic mitochondrion-targeting group and near-infrared (NIR) absorption was synthesized. After extending the photosensitizers' π conjugation via Knoevenagel reaction, both the absorbance and emission maxima of AmB X I shifted to the phototherapeutic wavelength range (650–900 nm). Theoretical computations indicate that the introduction of bromine atoms promotes spin–orbit coupling, so that for each additional bromine atom in AmB X I an increase in singlet oxygen quantum yield would be expected (0.3%, 2.2%, and 4.1%, for AmBHI, AmBMI, and AmBBrI, respectively). Moreover, AmB X I photosensitizers exhibited low cytotoxicity in the dark and high phototoxicity, with the half maximal inhibitory concentrations of AmBBrI found to be 46.93 nM and 22.84 nM, while those of AmBMI were 129.7 nM and 58.34 nM in HeLa and MCF-7 cancer cells, respectively. Notably, introduction of a single bromine atom was enough to produce a cytotoxic effect. Furthermore, the presence of a quaternary ammonium group in AmB X I enabled the dyes to localize and stain the negatively charged mitochondria. The results presented herein indicate the straightforward and facile synthesis of NIR-light triggered mitochondrion-targeting photosensitizers.